As metáforas do corpomídia em cena: repensando as ações físicas no trabalho do ator - Nunes, Sandra Meyer (2006)
This thesis analyzes metaphors that guide the concept of physical action in the work of an actor through the perspective of the cognitive sciences and the theory of body-media elaborated by professors Helena Katz and Christine Greiner in the graduate program of Communications and Semiotics at the Catholic University of São Paulo. The notion of action is essential to studies about the communication of the actor and is present in the genesis of theories of representation and in the modern concept of action. The pedagogy proposed by Constantin Stanislavski (1863-1938) by means of a method of physical actions, and later developed by Jerzy Grotowski (1933-1999), altered the processes of research and education for the actor. This study is based on the hypothesis that the approach to physical actions, proposed by both authors, revises the body-mind dualism in the work of the actor and points to issues now present in the cognitive sciences. By relating the system of physical actions of the actor with he studies of the body in the contemporary world, this study considers action as a procedural and dynamic system, from the perspective of a body-mind theory. The studies of philosophers and scientists António Damásio, Daniel Wegner, George Lakoff, Mark Johnson and Alain Berthoz are the foundations for the hypotheses presented about the metaphors that spark the action of the body and strengthen the theoretical-practical articulation needed to approach the problem of scenic action